APLIKASI AL-QUR’AN BERBASIS ANDROID MENGGUNAKAN METODE SEQUENTIAL SEARCH - Fina Faradila; Bambang Pramono; Nur Fajriah Muchlis (semanTIK, 2016)
This research was undertaken to design and implement Qur’an based on Android application using sequential search method, with the aim that can be read and understood anywhere in accordance with the functions of Android based devices, in this case is a cellular phone, it can be increase knowledge about sequential search methods also could be additional references. The method that used in this research had two methods that is data collection and application development. Data collection is done by study of literature.Advances in technology today, Qur'an can be read as much as possible. This condition can be satisfied by the existence of a solution to build Qur’an based on Android application using sequential search method, so it can be accessed anywhere.Based on the research results, in this case sequential search methods is suitable for searching data because the data is not based on the data sequences.  This application provides some features that are name of the surah, verse, translation, explanation background of the surah, and audio. Keywords— Al-Qur’an, Sequential Search, Android